Pengaruh Kompetensi, Penempatan Kerja dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Kantor Kecamatan Kendari Barat - Ambar Sari Wulele; Nasrul Nasrul; Asraf Asraf (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The strategic role of human resources in organizations has received great attention in today's era of globalization. The West Kendari Sub-district Office faces significant challenges related to competency, job placement, and human resource development that affect employee performance. This study aims to fill the knowledge gap by exploring the combined effect of the three variables on employee performance. The method used was a quantitative survey with a sample size of 33 respondents. The results showed that employee competence has the greatest influence on performance, followed by human resource development and job placement. Human resource development is proven to make a significant contribution in improving employee performance through continuous training programs. The combination of these three variables showed a greater influence than the influence of each variable separately, indicating the importance of an integrated and holistic approach to human resource management. This study provides empirical evidence that investment in the development of employee competencies and skills as well as proper placement is critical to achieving optimal performance. and ensure employee placement in accordance with employee expertise to improve performance